Hedonic Motivation and K-Pop Fandom: A Qualitative Observation and Analysis of Social Media Use - Roslan, Muhammad Amirul Asyraaf; Azmi Murad, Masrah Azrifah; Nasharuddin, Nurul Amelina (Journal of Techno-Social, 2024)
This study investigates the impact of Hedonic Motivation (HM) on SM engagement among K-pop fans. HM is one of the Unified Theory of Acceptance and Use of Technology (UTAUT) theoretical framework. Through a qualitative analysis of content shared by fans on platforms like X (formerly known as Twitter), the research identifies key themes such as Interactive Enjoyment, Emotional Connectivity, and Community and Social Bonds. The findings suggest that fans’ SM usage is significantly driven by the pleasure derived from interactive features, emotional satisfaction from recognition by their idols, and a strong sense of community. These motivations align with the UTAUT model, demonstrating how enjoyment shape behavioural intentions. The study provides practical insights for marketers and SM platforms to enhance user experience and engagement by leveraging these unique motivations, ultimately fostering deeper connections within this highly active and passionate demographic.